Determination of strain rate dependence at intermediate strain rates using acceleration information. (March 2023) - Kim, Ji-Min; Park, Jin-Seong; Leem, Do-Hyun; Kim, Minki; Barlat, Frédéric; Pierron, Fabrice; Kim, Jin-Hwan
Highlights: Utilizing acceleration for material characterization at intermediate strain rates. Virtual measurements obtained from a finite element simulation. A novel high-speed tensile tester based on elastic strain energy. High-speed camera and digital image correlation technique for high speed tensile test. The virtual fields method as an inverse problem methodology. Abstract: Precise stress-strain characteristics of materials for intermediate strain rates need to be utilized for analyzing various events in industry such as metal forging, sheet metal forming in manufacturing processes and automotive crash tests. However, the accurate evaluation of the load is not easy at intermediate or high strain rates, owing to the inertial effect. The present study aims at characterizing the hardening behavior using acceleration data without utilizing the load information with an application to a dual-phase DP980 steel sheet sample. Virtual measurements were obtained from a finite element model to check for the minimum acceleration magnitude necessary for stable identification. The same identification procedure as that used for the experiments was adopted. Also, a high-speed tensile testing equipment for steel sheet specimens was modified to increase the acceleration magnitude to implement the proposed methodology experimentally. The virtual fields method was chosen as an inverse tool to determine the strain-rate dependence of the sheet metal specimens. The stress–strain curve of an advanced high-strength steel at intermediate strain rates obtained from the acceleration was compared with the curve from the load data, and promising results were obtained.